A RESTful architecture for integrating decomposable delayed services within the web of things. (1st January 2011) - Ruppen, Andreas; Pasquier, Jacques; Hürlimann, T.
The web of things research activities consist essentially in developing concepts, tools and systems for creating and operating global networks of devices associated with embedded resources – RFID tags, sensors and even complex computing facilities – which are accessed by services. In that context, one of the most accepted standardisation technique in order to seamlessly integrate this huge set of heterogeneous services consists in RESTifying them. Whereas the integration of 'quickly computed' services is straight forward, the challenge remains for delayed, possibly decomposable services. We claim that this question represents an important challenge if one desires to enrich the potentialities of the web of things. In order to best contribute to its solution, this paper first proposes a classification of services into five categories with a special emphasis on tackling the problematic of the delayed and decomposable ones. It also advocates the use of WebSockets as the standard callback mechanism.